Insight into the reasons for the lack of Waqf reporting / Dalila Daud. - Daud, Dalila (Universiti Teknologi MARA Selangor, 2018)
This paper examines the attributes or factors contributing to the lack of reporting by Islamic councils. To gain feedback on how such problems can be solved, the researcher conducted interviews with experts from Islamic organisations. The findings of this paper may provide insights into how the waqf accounting is accepted by the Islamic Religious Council and the importance of the role of councils in ensuring transparency in reporting.